Oral nifedipine versus nitroglycerine patch for tocolysis in preterm labour - Sharma, Nidhi; Rani, Shikha; Huria, Anju; Chawla, Deepak (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Preterm delivery is a major cause of neonatal mortality and morbidity. Various modalities have been used to prediction of patient at risk of preterm labor. But due to multi-factorial etiology these predictors are not always useful. Tocolysis has a major role in arresting preterm labor. The purpose of this study was to compare the safety and efficacy of oral nifedipine with transdermal nitroglycerine in the inhibition of preterm labour. Methods: This single blinded randomized control trial was conducted in the labour room of department of Obstetrics and Gynecology from January 2011 to June 2012. One hundred women with singleton pregnancy between 28 weeks to 34 weeks preterm labour and no contraindication for tocolysis were enrolled in the study. After taking the informed consent subjects were randomized into two groups. Randomization was done by random number table. Fifty-one subjects in nifedipine group received oral nifedipine (Tab Depin 10mg). Forty-nine subjects receiving transdermal nitroglycerine patch (Nitroderm Patch 10) were included in NTG group. The variables analysed were delay in delivery for 48 hours, 7 days or more than 7 days, period of gestation at delivery and side effect profile of drugs. Results: The percentage of women delivering after 48hours of administration of nifedipine group (52.9%) and nitroglycerine group (53.1%). Failure of tocolysis, defined as delivery within 48 hours, with nitroglycerine group (32.7 %) was comparable to nifedipine (33.3 %). Headache was significantly higher in nitroglycerine group as compared to nifedipine group (p≤0.001). Maternal tachycardia was more common in nifedipine group compared to NTG group (p=0.001). Conclusions: Oral nifedipine and transdermal nitroglycerine have similar efficacy as tocolytic agent in patients with preterm labour.